Codes, Cryptology, and Information Security : First International Conference, C2SI 2015, Rabat, Morocco, May 26-28, 2015, Proceedings - In Honor of Thierry Berger - El Hajji, Said.; Nitaj, Abderrahmane; Carlet, Claude; Souidi, El Mamoun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the First International Conference on Codes, Cryptology and Information Security, C2SI 2015, held in Rabat, Morocco, in May 2015. The 22 regular papers presented together with 8 invited talks were carefully reviewed and selected from 59 submissions. The first aim of this conference is to pay homage to Thierry Berger for his valuable contribution in teaching and disseminating knowledge in coding theory and cryptography in Morocco since 2003. The second aim of the conference is to provide an international forum for researchers from academia and practitioners from industry from all over the world for discussion of all forms of cryptology, coding theory and information security.
Keywords: Computer security; Data encryption (Computer science).; Coding theory; Computer software; Computational complexity; Systems and Data Security; Cryptology; Coding and Information Theory; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science